2009
DOI: 10.1242/jcs.044032
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of human ER-exit sites: requirements for the localisation of Sec16 to transitional ER

Abstract: The COPII complex mediates the selective incorporation of secretory cargo and relevant machinery into budding vesicles at specialised sites on the endoplasmic reticulum membrane called transitional ER (tER). Here, we show using confocal microscopy, immunogold labelling of ultrathin cryosections and electron tomography that in human cells at steady state, Sec16 localises to cup-like structures of tER that are spatially distinct from the localisation of other COPII coat components. We show that Sec16 defines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
183
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(204 citation statements)
references
References 42 publications
20
183
1
Order By: Relevance
“…However, it does not preclude mitotic inhibition of interactions of Sec16 with downstream COPII components (AltanBonnet et al, 2006). Although the mechanisms underlying this inhibition remain unknown, these data also reinforce previous data showing that Sar1, Sec23-Sec24, Sec13-Sec31 all lie downstream of Sec16 (Ivan et al, 2008;Hughes et al, 2009). In fixed cells expressing Venus-Sec16AN, other COPII proteins, Sec24C ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, it does not preclude mitotic inhibition of interactions of Sec16 with downstream COPII components (AltanBonnet et al, 2006). Although the mechanisms underlying this inhibition remain unknown, these data also reinforce previous data showing that Sar1, Sec23-Sec24, Sec13-Sec31 all lie downstream of Sec16 (Ivan et al, 2008;Hughes et al, 2009). In fixed cells expressing Venus-Sec16AN, other COPII proteins, Sec24C ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Lentiviral transduction of FP-Sec16A was precluded by persistent recombination of the parent vector during cloning. Importantly, Venus-Sec16AN includes both the central conserved domain and upstream sequences shown to be necessary for membrane association and targeting to ERES (Ivan et al, 2008;Hughes et al, 2009). Specifically, it colocalises exactly with endogenous Sec16A and localises adjacent to Sec24C and Sec31A labelling, as is seen for endogenous Sec16A ); its expression does not alter the expression of endogenous Sec16A, and it rescues the phenotypes of decreased ERES number and Golgi fragmentation caused by suppression of endogenous Sec16A (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflected rapid ER exit dynamics, determined to be on the scale of seconds (Wilhelmi et al, 2016;Antonny et al, 2001;Forster et al, 2006;Sato and Nakano, 2005). There was also a small fraction of SEC16 (14%) adjacent to mature COPII structures (Hughes et al, 2009). Interestingly, overexpressing SAR1 T39N led to the dispersion of Wls throughout the cells and away from SEC16-positive exit sites.…”
Section: Export Of Wls Into Copii Vesicles Depends On Sar1 Activitymentioning
confidence: 98%
“…Recently, it was shown that monoubiquitinylation of Sec31 might regulate coats and would enable the formation of giant-sized COPII cages (Jin et al 2012). It should be noted that another architectural factor, Sec16, is also found at ER exit sites (ERESs) (Connerly et al 2005;Hughes et al 2009). Sec16 can interact with all COPII components; for example, contact with Sec13 is mediated by an ACE1 domain just as is seen in the interaction between Sec13 and Sec31 (Whittle and Schwartz 2010).…”
Section: The Cage Structures Of Vesicle Coatsmentioning
confidence: 99%